PENGARUH SUPPLIER RELATIONSHIP MANAGEMENT DAN CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP KINERJA BISNIS UMKM PAKAIAN JADI DI PEKANBARU - Sari Martia; Daulay Nauli Iwan; Siregar Andreas Prima (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to look at the effect of supplier relationship management andcustomer relationship management on business performance clothing SMEs inPekanbaru healt centers. The population in this study includes all SMEs at healtcenters, totaling 525 SMEs. The sample taking technique was using conveniencesampling so obtained sample of 84 respondents. The dependent variable (Y) inthis study was business performance the independent variable is supplierrelationship management (X1), customer relationship management (X2). Theanalisys method was multippled regression linier berganda. For data processingwas using SPSS 23. The resultsof research shows that : 1) supplier relationshipmanagement and customer relationship management have a significant effect onbusiness performance, 2) there significant effect of Supplier relationshipmanagement on the business performance, 3) there significant effect of customerrelationship management on the business performance. Keywords : Supplier Relationship Management, Customer RelationshipManagement, Business Performance